Albendazole therapy reduces serum zinc in elementary school children with Ascaris lumbricoides infections - Buana, Ria; Kalumpiu, Jane Florida; Djuardi, Yenny; Supali, Taniawati (Universa Medicina, 2016)
BackgroundSoil-transmitted helminth (STH) infection can cause malnutrition and vice versa, and decrease serum zinc concentrations. No previous studies were found on the effect of STH treatment on serum zinc concentrations in elementary school children. The objective of this study was to evalaute the effect of STH treatment on serum zinc concentration in elementary school children in Jakarta. MethodsA pre-experimental study (one group pre and post) was conducted on 3rd - 5th grade students in one elementary school in North Jakarta. FLOTAC examination was used to determine infection status and STH intensity, while serum zinc concentrations were measured by atomic absorption spectrometry. All children were given albendazole 400 mg for three consecutive days. Stool and blood samples were collected before and three weeks after treatment with albendazole. A paired t test was used to analyze the data. ResultsThe STH prevalence was 63.4%; these were mainly Ascaris lumbricoides and Trichuris trichiura infections. Before treatment, children infected with A.lumbricoides and T.trichiura had significantly higher serum zinc concentrations (p=0.028; p=0.014). After treatment, children with A.lumbricoides had significantly lower serum zinc concentrations (p=0.039), while children with T.trichiura had slightly lower serum zinc concentrations (p=0.659) than before treatment. ConclusionsAlbendazole treatment produces lower serum zinc concentration in elementary school children with A.lumbricoides infections. A profound understanding of the interaction between helminth infections and zinc may assist in guiding integrated and sustainable intervention strategies among affected children throughout the world.